Sex‐dependent role of Pannexin 1 in regulating skeletal muscle and satellite cell function. Issue 10 (8th August 2022) - Freeman, Emily; Langlois, Stéphanie; Scott, Kaylee; Ravel‐Chapuis, Aymeric; Jasmin, Bernard J.; Cowan, Kyle N.
Abstract: The development and regeneration of skeletal muscle are mediated by satellite cells (SCs), which ensure the efficient formation of myofibers while repopulating the niche that allows muscle repair following injuries. Pannexin 1 (Panx1) channels are expressed in SCs and their levels increase during differentiation in vitro, as well as during skeletal muscle development and regeneration in vivo. Panx1 has recently been shown to regulate muscle regeneration by promoting bleb‐based myoblast migration and fusion. While skeletal muscle is largely influenced in a sex‐specific way, the sex‐dependent roles of Panx1 in regulating skeletal muscle and SC function remain to be investigated. Here, using global Panx1 knockout (KO) mice, we demonstrate that Panx1 loss reduces muscle fiber size and strength, decreases SC number, and alters early SC differentiation and myoblast fusion in male, but not in female mice. Interestingly, while both male and female Panx1 KO mice display an increase in the number of regenerating fibers following acute injury, the newly formed fibers in male Panx1 KO mice are smaller. Overall, our results demonstrate that Panx1 plays a significant role in regulating muscle development, regeneration, and SC number and function in male mice and reveal distinct sex‐dependent functions of Panx1 in skeletal muscle.